POLA LUKA KORBAN KECELAKAAN LALU LINTAS PADA PEJALAN KAKI DAN PENGENDARA SEPEDA MOTOR - Dini Indriani; Kunthi Yulianti (E-Jurnal Medika Udayana, 2015)
PATTERNS OF INJURY TRAFFIC ACCIDENT VICTIMS IN PEDESTRIAN AND MOTORCYCLISTTraffic accident has become one of the health problems in the world. In Indonesia the highest cause of death in traffic accident was motorcycle (35.7%), the second was others/unspecified road users (35.4%) and the third was pedestrians (21.1%). Analysis patterns of injuries play a role in determining the manner of death. The study aimed to describe the sociodemographic and pattern of injury traffic accident victim in pedestrians and motorcyclists as well as whether was there any differences or similarities of pattern of injury in both groups. The study design used a descriptive and comparative analysis with Chi Square test. The result, we obtained 65 cases of death in motorcyclists (n=42) and pedestrians (n=23). The number of victims was higher in men than women in both group. In pedestrian the victims were 40-64 years old followed by 17-39 years old and > 64 years old.In motorcyclists the victims were 17-39 years old, followed by 40-64 years old and 11-16 years old. The most frequent types of injuries wasabrasion, but the types of injuries that has significant difference was fracture where motorcyclists often suffer fractures (66.7%) than pedestrians (43.5%). The most common site of injury in both group were head, upper extremities and lower extremities. There were no significant difference of both groups. However, the site of injury which had significant difference was chest injury, where motorcyclists often suffer chest trauma (54.8%) than pedestrians (30.4%).